Green Enzymatic Decaffeination of Robusta Coffee Using Bromelain from Pineapple Peel for Sustainable Processing - Yunita, Imelda; Rossi, Evy; Hamzah, Farida Hanum; Nopiani, Yanti (Department of Agro-industrial Technology, University of Brawijaya, 2026)
AbstractRobusta coffee contains relatively high levels of caffeine, so consumption should be limited due to potential health risks if consumed excessively. This condition drives the development of effective, safe, and sustainable decaffeination technologies. Enzymatic decaffeination using a crude bromelain extract from pineapple peel offers a green chemistry approach that uses natural biocatalysts and agricultural waste. This study aimed to determine the optimal concentration of crude bromelain extract to reduce caffeine content in Robusta coffee beans and to evaluate its effects on moisture content, ash content, pH, and color brightness. A completely randomized design with one factor and six bromelain concentrations (0–50%) with three replications was applied. Data were analyzed using analysis of variance followed by Duncan’s multiple range test at a significance level of 0.05. The results showed that increasing bromelain concentration consistently reduced caffeine content from 2.74% to approximately 0.21% at 5% concentration. The pH and color brightness decreased as the enzyme concentration increased. The moisture content increased but remained below the national quality standard, whereas the ash content decreased, indicating mineral leaching during the enzymatic process. A crude bromelain concentration of 50% was considered practically optimal, achieving significant caffeine reduction with manageable physicochemical changes. These findings highlight the potential of scalable, efficient green decaffeination to support a sustainable, low-caffeine Robusta coffee industry.Keywords: bromelain, enzymatic decaffeination, green chemistry, Robusta coffee, pineapple peel AbstrakKopi Robusta memiliki kadar kafein relatif tinggi sehingga konsumsinya perlu dibatasi karena berisiko menimbulkan gangguan kesehatan jika dikonsumsi berlebihan. Hal ini mendorong pengembangan teknologi dekafeinasi yang efektif, aman, dan berkelanjutan. Dekafeinasi enzimatik menggunakan ekstrak kasar bromelain dari kulit nanas berpotensi menjadi pendekatan green chemistry melalui pemanfaatan biokatalis alami dan limbah pertanian. Penelitian ini bertujuan menentukan konsentrasi optimal ekstrak kasar bromelain untuk menurunkan kadar kafein biji kopi Robusta serta mengevaluasi pengaruhnya terhadap kadar air, kadar abu, pH, dan tingkat kecerahan warna. Percobaan disusun menggunakan rancangan acak lengkap satu faktor dengan enam taraf konsentrasi bromelain (0–50%) dan tiga ulangan. Data dianalisis menggunakan analisis ragam dan uji lanjut Duncan multiple range test pada taraf signifikansi 0,05. Hasil menunjukkan peningkatan konsentrasi bromelain menurunkan kadar kafein secara konsisten dari 2,74% hingga sekitar 0,21% pada konsentrasi 5%. Nilai pH dan kecerahan warna menurun seiring peningkatan konsentrasi enzim. Kadar air meningkat namun tetap di bawah standar mutu nasional, sedangkan kadar abu menurun yang mengindikasikan pelindian mineral selama proses enzimatik. Konsentrasi ekstrak kasar bromelain 50% dinilai paling optimal secara praktis karena menghasilkan reduksi kafein signifikan dengan perubahan mutu fisikokimia yang masih dapat dikelola. Temuan ini menunjukkan potensi penerapan dekafeinasi hijau yang efisien siap ditingkatkan skalanya dan mendukung keberlanjutan industri kopi Robusta rendah kafein.Kata kunci: bromelain, dekafeinasi enzimatik, green chemistry, kopi Robusta, kulit nanas